2014
DOI: 10.1145/2643132
|View full text |Cite
|
Sign up to set email alerts
|

Privacy, anonymity, and big data in the social sciences

Abstract: Quality social science research and the privacy of human subjects require trust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 9 publications
0
65
0
Order By: Relevance
“…Privacy remains a burning issue in the age of big data due to monetization and sharing of data. Social actors, including users and citizens, are increasingly concerned about the amount of information shared about them and the compromises they need to make to use a particular service [32,77]. Thus, this research area needs to be tackled from legal, technical and social perspectives.…”
Section: Discussion and Research Agendamentioning
confidence: 99%
See 1 more Smart Citation
“…Privacy remains a burning issue in the age of big data due to monetization and sharing of data. Social actors, including users and citizens, are increasingly concerned about the amount of information shared about them and the compromises they need to make to use a particular service [32,77]. Thus, this research area needs to be tackled from legal, technical and social perspectives.…”
Section: Discussion and Research Agendamentioning
confidence: 99%
“…Since our BDA definition covers social and ethical values, privacy preservation must form an essential pillar of big data activities within service ecosystems. To date, efforts done towards privacy preservation of service users have always been met with a compromise on the quality of studies in the fields of social sciences [11] [13][32] [77].…”
Section: The Infrastructurementioning
confidence: 99%
“…For example, researchers at MIT and Harvard drawing on their edX 12 experience showed that anonymization weakened the results of their analysis of student data. Accordingly, they suggested confidentiality policies that compel researchers with full data access to uphold the privacy of the human subjects [29].…”
Section: Alternatives To Anonymitymentioning
confidence: 99%
“…Ever increasing computational power may make data collection that is respecting today's privacy requirements entirely retraceable to the personal level within a few years. Attempts to make the de-identification process more robust may diminish the utility of the data (Daries et al, 2014). Again, it may not come unexpected that many, not in the least data subjects themselves, such as teachers, students, and their parents, are reluctant to the use of big data in education.…”
Section: Introductionmentioning
confidence: 99%